The reinforcement of styrene butadiene rubber composites with simple environmentally friendly aramid fiber modification. Issue 3 (27th December 2020) - Ji, Yongchun; Liu, Chunli; Luo, Zhu; Zhong, Jincheng; Yin, Lianpeng
Abstract: The surface treatment of aramid fiber (AF) improved the properties of reinforced composites. However, many AF modification methods were difficult to apply to the mass production of reinforced composites due to drawbacks, such as processes that were complex and not environmentally friendly. This paper described three simple and environmentally friendly methods for AF surface treatment and their effects on the properties of reinforced aramid fiber/carbon black/butadiene benzene ethylene rubber (AF/CB/SBR) composites. The AF was treated by thermal oxidation and coated with butadiene‐styrene‐pyridine rubber latex (VPL) or maleated polybutadiene liquid rubber. Then, AF/CB/SBR composites were produced when the modified AF was introduced into the SBR matrix. The results showed that compared with that of the composite with untreated AF, the interfacial bonding between the modified AF and the rubber matrix was improved, especially for tensile modulus elongations of 100% and 300%, and the tear strength of the composites was enhanced. Compared with those for the rubber composites with the AF treated by thermal oxidation, the mechanical properties of the rubber composites with the coated AF showed a greater improvement, but the heat generation was higher. Moreover, the thermal oxidation method not only improved the constant elongation stress and tear strength but also reduced the heat generation of the materials. Abstract : Three simple and environmentally friendly methods for AF to enhance SBR composites.